(untitled) (Research, Society and Development, 2023)
The benefits of breastfeeding for the child and the mother are already well established in the literature. Recent studies indicate that the consequences of early weaning can affect not only childhood, but also adolescence and adulthood. Possible late consequences include an increased occurrence of long-term common mental disorders (CMD). However, there are few available data on this topic, which makes it necessary to carry out more research that seeks to evidence the association between breastfeeding and mental disorders. Therefore, this study aimed to carry out a literature review in order to relate early weaning with the occurrence of CMD. The search was carried out on the search portals PubMed, CENTRAL, SciELO and Lilacs. After searching with the descriptors, 3 articles were selected that matched the inclusion and exclusion criteria. The results indicate that prolonged breastfeeding has a protective effect on the mental health of adolescents and adults, being associated with lower risks of CMD occurrence.